Kesesuaian Biaya Riil Terhadap Tarif INA-CBG’S Pasien Diabetes Melitus Rawat Inap di RSUD Kota Kotamobagu Tahun 2024 - Nanda Sayyida Begum; Windi Astuti; Moh. Rasyid Kuna (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: The high prevalence of diabetes mellitus and its associated complication risks potentially increase the financial burden of healthcare. Therefore, evaluating the alignment between actual care costs and INA-CBG's rates is necessary to support the sustainability of the National Health Insurance (JKN) financing system. Objective: This study aimed to analyze the alignment between actual care costs and INA-CBG's rates for inpatient diabetes mellitus patients and to identify factors influencing any discrepancy at RSUD Kota Kotamobagu. Methods: This was an observational study with a cross-sectional design and a retrospective approach. A sample of 83 patients was selected using simple random sampling from the population of JKN-insured inpatients with diabetes mellitus from January to December 2024. Data were analyzed using a paired t-test to compare actual costs with INA-CBG's rates, and multiple linear regression to identify factors affecting the cost difference. Results: The mean actual care costs for class I, II, and III were IDR 6,882,567, IDR 5,282,412, and IDR 5,224,188, respectively. All treatment classes showed negative differences (actual costs higher than INA-CBG's rates), but a statistically significant difference was found only in class III (p = 0.000). Regression analysis revealed that length of stay (LOS) was the only factor significantly influencing the cost difference (p = 0.002; coefficient B = 1,250,000), while age, comorbidities, and class of care showed no significant effect (p > 0.05). Conclusion: There is a significant discrepancy between actual costs and INA-CBG's rates in class III care, with length of stay as the main determining factor. Hospitals should consider adjustments in inpatient management and tariff evaluation, particularly for cases with longer LOS.